The Effect Of Knowledge Transfer And Family Environment On Business Sustainability Family In Cemara Asri Medan - Mellisa Angelie; Inneke Qomariah Lubis (Journal Of Management Analytical and Solution (JoMAS), 2022)
The difficulty of building a new business is a must for business owners to get a successor. The problem of family business sustainability from the beginning is often the business that was painstakingly established by the first generation to be lost in the second or third generation so for now the sustainability of family businesses has always been a special concern for families. With the transfer of knowledge, of course, it will be an added value in advancing the family business and it is not surprising that many families try the knowledge of their successors first before actually giving up their business to the successors. In addition, in continuing the business, support from the family environment is very important for the successor because in addition to being able to provide encouragement, the family environment can also provide a sense of security for the successor to study well because there is still supervision from the family before it is actually managed directly by him. alone. This research uses quantitative descriptive research. The data analysis technique that will be used in this research is multiple linear regression analysis. The measurement scale used is a Likert scale. Simultaneously or partially there is a significant influence between the variables of knowledge transfer and family environment on business sustainability in Cemara Asri Medan.